Subjective acoustic measures and speech intelligibility in churches - António P. O. Carvalho (1996)
Subjective studies of existing churches in Portugal are part of a research program conducted to explore methods to evaluate, predict, and preview the acoustical qualities of churches. This included both evaluating live musical performances in 36 churches and speech intelligibility testing. This work is characterized by the use of sample of listeners, evaluation of several locations in each room, assessment of many rooms and comprehensive statistical analysis of the data. The limitations using this type of performance for evaluations are fully realized. The acoustical response of the church mutates when it is fully occupied. The character of the music heard during a religious service or during an actual musical performance is also different.